2006
DOI: 10.1080/14622200600670454
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of pro‐tobacco and anti‐tobacco messages on adolescent smoking susceptibility

Abstract: We examined the longitudinal impact of self-reported exposure to pro- and anti-tobacco media on adolescents' susceptibility to smoking, using in-school surveys from a culturally diverse sample. Ethnicity and acculturation also were examined as potential moderators. Middle-school students (N = 2,292) completed self-report questionnaires during the 6th, 7th, and 8th grades. Chi-square analyses were conducted to determine whether reported exposure to pro- and anti-tobacco media varied according to ethnicity, accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 47 publications
4
76
0
1
Order By: Relevance
“…16 We believe that our results complement others' analyses of tobacco use patterns. The influential roles of tobacco-related media 18 and targeted cigarette advertising 30,31 on adolescents' tobacco use patterns have been previously noted. Likewise, perceptions of a lack of tobacco addictiveness have correlated with adolescent tobacco use.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…16 We believe that our results complement others' analyses of tobacco use patterns. The influential roles of tobacco-related media 18 and targeted cigarette advertising 30,31 on adolescents' tobacco use patterns have been previously noted. Likewise, perceptions of a lack of tobacco addictiveness have correlated with adolescent tobacco use.…”
Section: Figurementioning
confidence: 99%
“…17 For example, previous research has noted that social norms and exposure to tobacco-related media influence adolescents' later tobacco use patterns, probably by influencing how individuals perceive such products. 17,18 Recent research has demonstrated associations between youth perceptions of comparative harm and tobacco product use in the cases of light and intermittent smoking patterns 19 and e-cigarettes. 20 -22 Perceptions of relative safety regarding e-cigarettes may lead to unintended consequences.…”
mentioning
confidence: 99%
“…21 Perception of tobacco influences youths' behaviors over time. Exposure to pro-and antitobacco media 22 and perceptions of secondhand smoke, 23 for example, alter adolescents' affinities toward tobacco use. Because 9 out of 10 smokers begin smoking as adolescents, 24 understanding adolescents' perception of light and intermittent smoking may be particularly helpful in assessing which individuals may benefit from targeted public health and clinical interventions.…”
mentioning
confidence: 99%
“…6 Youth who are exposed to retail tobacco marketing are also more likely to experiment with smoking and to become smokers. [7][8][9][10][11][12][13][14][15][16] The Family Smoking Prevention and Tobacco Control Act of 2009 gives states and local governments legal authority to regulate the time, place, and manner of tobacco advertising. As states consider policies such as banning the display of tobacco products, empirical studies are needed to determine the potential impact of these regulations.…”
Section: Discussionmentioning
confidence: 99%